Periodontal Diagnosis in a Young Patient with an Unusual Presentation of Dental Calculus - Khansa Taha Ababneh; Sultan Al Nafisah; Manal Maslamani; Turki Al Asiri (Journal of Pharmacy and Bioallied Sciences)
This report details the periodontal diagnosis and phase I treatment of an 18-year-old male patient dissatisfied with his teeth. The patient, on 20 mg Isotretinoin for acne, exhibited heavy calculus and plaque, generalized gingival inflammation, carious lesions, remaining roots, an anterior open bite, bilateral cross-bite, and an ectopically erupted tooth (#25). Initial scaling enabled examination, revealing FMPS and FMBS of 100%, PD of 1–7 mm, gingival recession of 1–2 mm, a maximum CAL of 6 mm, and radiographic bone loss of around 48% of teeth, reaching up to 15% of the root length. Diagnosed with generalized periodontitis (stage II, localized stage III, grade B), treatment involved patient education, scaling, selective root planning, and a long-term maintenance plan. At reevaluation, the patient showed improved oral hygiene, reduced FMPS (33%) and FMBS (11%), fewer pockets, and decreased PD and CAL (deepest CAL now 6 mm). Early periodontal intervention and consistent oral hygiene are critical for subsequent dental treatments.